Pemberdayaan Lansia Melalui Pemberian Daun Seledri Sebagai Upaya Pengendalian Hipertensi - Cahya Tribagus Hidayat; Hera Puspita Anggarini; Icha Nur Safitri; Fadhilah Anggrelia Rifdahyanti; Muhammad Gimnastiar Reza P; Izzaturrohmah Senna Adistya; Wahyu Andrean Basita Putra; Ardhi Gigih Prasojo; Eric Pratama Widianto (Utami Publisher, 2026)
Hypertension is a common public health issue found among adults and the elderly at the community level. The lack of routine blood pressure monitoring and limited understanding of nonpharmacological therapies pose challenges in managing hypertension. This community service activity aims to improve community knowledge and empowerment in the management of hypertension through education and demonstrations of celery leaf decoctions as complementary therapies. The activity was conducted in Kaliwining Village, Rambipuji Subdistrict, Jember Regency, on February 4 and 9, 2026, targeting adults and the elderly. The methods used included health screening (blood pressure, weight, and height measurements), interactive counseling on hypertension management, and a demonstration of preparing acelery leaf decoction. The results of the activity showed active participant engagement,the identification of participants with high blood pressure, and improved understanding of risk factors, complications, medication adherence, and lifestyle modifications. Participants were able to recap the material presented and demonstrated interest in applying non-pharmacological therapy at home. This activity was effective in raising awareness and empowering the community in the management of hypertension.